Analytic study of indications, outcomes and complications of percutaneous liver biopsy at Tishreen University Hospital - janoudi, nourshan; Zizfoun, Hassan; Dughman, Daad (Latakia University Journal -Medical Sciences Series, 2022)
Background: Despite significant improvements in other less invasive diagnostic techniques, histological assessment of the liver remains an essential tool in establishing the diagnosis in numerous disease in combination with various clinical and laboratory data. Aim: The purpose of this study was to characterize the indications of performing percutaneous liver biopsy. In addition to, detecting the rate of complications following the procedure. Materials and Methods: This was a Prospective Observational Analytical study involving 175 patients undergoing liver biopsy at Gastroenterology unit, Internal Medicine Department, Tishreen University Hospital, Lattakia, during the period between April 2020-April 2021. Results: Out of 175 patients, 93 were male and 82 were female. Mean age of the patients was 53.03±12.1 without significant differences according to gender. The most common indication of biopsy was presence of mass lesions (74.9%), and liver metastasis was the most frequent histological finding (35.4%). Thirty-three patients (18.9%) presented with complications, pain was the most frequent complication (10.8%), followed by bleeding (3.4%), pneumothorax (2.3%), hypoxia and hypotension (1.7%), with one reported case of death (0.6%). Pain was associated significantly with age in which was more frequent in young patients(p:0.001), and the indication of biopsy in which was more common in presence of mass lesions (p:0.04) Conclusion: Liver biopsy is a safe and valuable procedure in diagnosis and management of patients with liver diseases with low rate of complications when performed correctly and taking into consideration contraindications.